The Effect Of Cash Ratio, Debt To Equity Ratio, And Total Asset Turnover On The Profit Growth Of Technology Companies Listed On The Indonesian Stock Exchange - Syifa Julita Moulinda; Novita Sari; Chornelia Putri Indah Wijaya (Journal of Strategic Behaviour Accounting, 2026)
This study aims to analyze the impact of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TOTA) on Profit Growth. The research subjects were technology companies listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. Using purposive sampling and multiple linear regression analysis, a total of 70 observations (N=70) were analyzed. The results of the study show various findings. Simultaneously (F-test), the three variables (CR, DER, TOTA) were proven to have a significant effect on Profit Growth (Sig. 0.001). However, partially (t-test), only the Current Ratio showed a positive and significant effect (Sig. 0.001). The other two variables, Debt to Equity Ratio (Sig. 0.897) and Total Asset Turnover (Sig. 0.091), were found to have no significant effect. The model's ability to explain Profit Growth was limited, with an Adjusted R Square value of 18.2%. The remaining 81.8% was influenced by factors outside the scope of this study. This conclusion indicates that in the technology sector, liquidity (CR) is a significant predictor of Profit Growth, while conventional solvency ratios (DER) and asset efficiency (TOTA) do not show the same impact.